The interaction between gut microbiota and flavonoid extract from Smilax glabra Roxb. and its potent alleviation of fatty liver. Issue 17 (8th July 2021) - Zhao, Lei; Qi, Ziyan; Yi, Ling; Li, Jingjing; Cui, Yadong; Ur Rehman, Faiz; Yang, Jianhua; Liu, Jiangyun; Li, Yali; Zhang, Jian
Abstract : The flavonoid extract from Smilax glabra Roxb. (FSGR) and its metabolites probably could be used as prebiotic agents to impede gut dysbiosis and fatty liver-related metabolic disorders. Abstract : Fatty liver is associated with intestinal microbiota dysbiosis and low-grade chronic inflammation. Herein we report the interaction of the flavonoid extract from Smilax glabra Roxb. (FSGR) with gut microbiota. Then, FSGR's function of modulating microbiota in a rat model of high-fat diet (HFD) induced fatty liver has been explored. These investigations indicated that the main compound in FSGR, such as astilbin and its isomers, could be metabolized to aglycone, while further splitting resulted in some phenolic acid compounds through a redox reaction. The data obtained clearly showed that FSGR not only alleviated the steatosis degree of liver cells and modulated the contents of short chain fatty acids (SCFAs) in the intestinal tract, but also reversed gut dysbiosis induced by HFD as prognosticated by the decreased ratio of Firmicutes / Bacteroidetes (F/B) and altered gene expression. The results demonstrated that FSGR probably could be used as a prebiotic agent to impede gut dysbiosis and fatty liver-related metabolic disorders.